Evaluation of Financial Inclusion and Financial Well-Being in expanded BRICS economies - Manoj Kumar; Nasser Al Muraqab; Prashanth Bshivanna; Immanuel Azaad Moonesar; Udo Christian Braendle; Ananth Rao (Foresight and STI Governance)
Most of the challenges to sustainable development are interconnected and systemic in nature, which makes achieving this goal particularly challenging. Research on these barriers and their solutions revealed that neither technological nor social innovation hinders the adoption of this development model. The main reason lies in the specific mechanisms for overcoming inertia, resistance to change, path dependency, and entering a new trajectory. One of the key spaces where the widest circles of the population are in close contact with new technologies is the financial sector. Fintech has significant potential to overcome these limitations, change behavioral patterns, reduce path dependence, and launch development on a new trajectory. The article provides a comprehensive analysis of these processes using the example of the expanded BRICS countries. It compares heterogeneous socioeconomic landscapes and assesses the readiness of the countries in question to master more complex development models, using digital banking as an example. The study identifies the blocking factors and suggests ways to overcome them. An interdisciplinary synthesis of the theories of narrative persuasion, evolutionary governance, and path dependence provides a new understanding of the interaction of financial systems, governance structures, and social behavior, upon which financial inclusiveness depends as a cornerstone for achieving balanced economic growth.